2016
DOI: 10.1186/s12943-016-0512-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma: microRNA expression profiling and integrative analyses for elucidation of tumourigenesis mechanism

Abstract: BackgroundThe advantages and utility of microRNAs (miRNAs) as diagnostic and prognostic cancer markers is at the vanguard in recent years. In this study, we attempted to identify and validate the differential expression of miRNAs in oral squamous cell carcinoma (OSCC), to correlate their expression with the clinico-pathological profile of tumours and to identify the signaling pathways through which the aberrantly expressed miRNAs effect tumourigenesis.MethodsmiRCURY LNA™ array with probes specific to 1168 miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 80 publications
5
143
1
2
Order By: Relevance
“…Ning Y, et al, found that let-7d was downregulated in ovarian cancer tissues compared with normal ovarian tissues [22]. Let-7d was also reported to be downregulated in oral squamous cell carcinoma [33] and renal cell carcinoma [24], which was consistent with our results in breast cancer. However, in some cases of head and neck squamous cell carcinoma (HNSCC), let-7d was significantly upregulated in tumor tissue [34].…”
Section: Discussionsupporting
confidence: 91%
“…Ning Y, et al, found that let-7d was downregulated in ovarian cancer tissues compared with normal ovarian tissues [22]. Let-7d was also reported to be downregulated in oral squamous cell carcinoma [33] and renal cell carcinoma [24], which was consistent with our results in breast cancer. However, in some cases of head and neck squamous cell carcinoma (HNSCC), let-7d was significantly upregulated in tumor tissue [34].…”
Section: Discussionsupporting
confidence: 91%
“…Oral carcinogenesis arises through the accumulation of genetic and epigenetic changes, including alterations in the expression of coding and non-coding RNAs (3,4). Oral cancer types express a specific miRNA portfolio, which contributes to maintain the epithelial characteristics of the cells (5,6). …”
Section: Introductionmentioning
confidence: 99%
“…By analysis of the miRNA expression profiles of OSCC tumors and normal oral mucosal samples, Soga’ et al showed that OSCC tissues have a unique miRNA profile pattern when compared with that in normal tissues [8]. In another study, Manikandan’ et al identified 46 miRNAs that were differentially expressed in OSCC [9]. Likewise, Siow’ et al identified 15 upregulated and 4 downregulated miRNAs in OSCC as compared with normal tissues and miR-375 was validated as the most down-regulated miRNA [10].…”
Section: Introductionmentioning
confidence: 99%